Analysing strength, hardness and grain-structure of 0.2%-C steel specimens processed through an identical heating period with different continuous transformation rates. (1st December 2022) - Dewangan, Saurabh; Singhal, Prakrit; Selvaraj, Senthil Kumaran; Dev, S Jithin; Swathish, R Srii; Cheepu, Muralimohan; Legutko, Stanislaw; Adefris, Addisalem; Chattopadhyaya, Somnath; Chadha, Utkarsh
Abstract: The present work deals with improvement of mechanical properties and refining the microstructure of low carbon steel (0.2%-C) after applying heat treatment techniques. For the purpose, five different samples were taken under study. First sample was kept in 'as received' condition and other four samples were undergone into heating process in an Induction furnace. The holding temperature of all the four samples were kept common i.e., 850 °C for a fixed period of 2.5 h. Then, these four samples were cooled into four different cooling media i.e., Air, Water, Oil, and Furnace. All the samples were in the form of rods with 195 mm length and 32 mm diameter. The universal testing machine was used to determine the tensile strength of all the samples. Rockwell hardness tester was used to find the hardness of samples. The microstructural variation was analysed through an optical microscope. All the results were analysed and compared with 'as received' sample. The Oil cooled sample showed the highest tensile strength of 585 MPa. The microstructural orientation of oil cooled sample i.e., bainite + fine lamella of ferrite and cementite, provides a good hardness, strength, and toughness to the steel. In addition, XRD and fractography analysis of the samples were also carried out.